(untitled) (Fiep Bulletin - online, 2014)
ntroduction: Diabetes is a world health problem and physical exercise can help at the treatment of it.Aim: The aim of this study was to evaluate if patients with diabetes mellitus type 2 (DM2) are able to reduce the blood glucose level after acute resistance training in high and moderate intensity. Methodology: A total of 20 male patients with DM2 were selected, 10 to each group, and with age between 54±8 years. One of the groups did the training protocol at a 60% (D-60) and the other at 75% (D-75) of the maximum load.Blood glucose was checked by capilaris using a glucose meter of the brand Accu-chek Active-Roche 30 minutes prior to the exercise protocol and right after the training. It was calculated the mean, standard deviation, standard error, and absolute delta to show the variance between before and after training. Kolmogorov-Smirnov was done to check the normality of the sample. Student T test was done. It was adopted p<0,05. Results: In group D-60 blood glucose level before training was 127,4±14,59 mg/dL and after 126,1±12,59 mg/dL, variation of -1,3±2 mg/dL. At D-75 the blood glucose before the exercise was 134,4±12,03 mg/dL and after 129,1±11,22 mg/dL, with a variation of -5,3±7,98 mg/dL. There was significative difference between before and after the protocol training just in group D-75 (p<0,001). Theacuteresistance exercise done in high intensity presented greater glycemic reductionwhen compared tomoderated(p <0,05).Conclusion: High intensity acute resistance training is a better controller of blood glucose in people with DM2.